Sustainable Development on Household Waste Management in Batu Pahat, Johor - JAMIL, ASHYRA; Jailani, Junaidah (Recent Trends in Civil Engineering and Built Environment, 2021)
Sustainable Development (SD) is a phenomenon that emerged in the 1970s when major development programs were undertaken by the developing world in terms of cutting, clearing forests, constructing elevated buildings and spacious highways. A sustainability is then needed to develop without endangering the needs of the future generations since it impacts the natural environment. For this study, the scope of research done is focused on residential area in Taman Melewar, Parit Raja which consist of 130 residential houses. This paper focusing on proper household waste management in sustainable approaches. This study was carried out by a questionnaire, Google Form that distributed online using social media platform that is more preferred during this pandemic. A set of 100 response from the resident is received. As a result, the current household waste management were identified and the level of awareness of the respondents towards the sustainable household management is identifies as high, even though only partial of the respondent does separate their waste as a way to a sustainable waste management. Several recommendations are needed to be done in order to increase the application of sustainable household management among residents.